Phylogeny and taxonomy of the Pacific monitor lizards (Squamata: Varanus: Euprepiosaurus) - Weijola, Valter (fi=Turun yliopisto|en=University of Turku|, 2017)
The monitor lizards of the subgenus Euprepiosaurus Fitzinger, popularly known as the Pacific monitor lizards, are widely distributed on islands in the southwest Pacific region where they often form conspicuous components of the local faunal communities. Despite their notable size, importance as top predators, and the widespread use of their meat and skins by local communities, the number of species, phylogenetic relationships, and distribution of these lizards have remained poorly known. Most species have been described recently and known to science only from colonial-era museum collections or from animals reaching Europe through the international pet trade. The number of recognized species has risen from two to fourteen since 1990, both as a result of revisions of populations previously assigned to Varanus indicus, and from the discovery of completely new species. This dissertation investigates the phylogenetic relationships and taxonomy of Euprepiosaurus throughout its extensive geographical range. It relies on a combination of molecular, morphological, and field data to reveal species boundaries and species distributions. Tissue samples were collected over twelve months of fieldwork in the Papua New Guinean island provinces, and sampled from existing museum collections. The results are presented in four separate chapters (one manuscript and three published articles). The first chapter is the most well-sampled molecular phylogeny of the subgenus Euprepiosaurus and Hapterosaurus Bucklitsch to date. It includes 96 samples representing 14 recognized species and several apparently new species. Two mitochondrial genes (ND4 and 16S) were sequenced and Maximum Likelihood, Parsimony and Bayesian inference approaches were used for phylogenetic reconstructions. BEAST was used to estimate lineage divergence times. All analyses retreive both Euprepiosaurus and Hapterosaurus as monophyletic. Within Euprepiosaurus three clades, or species-groups, are recovered as monophyletic with varying support. These are the V. doreanus group, the V. indicus group, and the V. jobiensis group (currently consisting of a single species). The V. doreanus group consist of four recognized species – all of which are well-supported and monophyletic in our analysis. Varanus doreanus which is geographically widespread on New Guinea, Cape York, Aru and other satellite islands positions as a sister taxon to a clade containing the single-island endemics V. finschi, V. semotus and V. yuwonoi. The V. indicus group is estimated to have radiated rapidly during the Pleistocene, resulting in a number of allopatric island endemics. Varanus indicus is the most widespread species and occurs throughout New Guinea and its offshore islands, New Britain, Cape York and parts of the Northern Territory. Other well supported monophyletic lineages include V. cerambonensis, V. melinus, V. douarrha, and several apparently new species from insular PNG, the Solomon Islands, Western Micronesia, and the Moluccas. The Varanus jobiensis specimens included in this study are resolved as a well-supported monophyletic clade consisting of several divergent lineages. The populations from the western and eastern part of the range are estimated to have diverged 3-7 million years ago, suggesting that V. jobiensis may represent a species complex. The second chapter is a study of the identity of V. indicus. Described by Francois Daudin in 1802, the original type specimen has since been lost and more recently replaced by a neotype. Field and museum studies (this study) indicate that the neotype neither originates from the type locality, nor does it represent the species described by Daudin. An application has therefore been made to the ICZN to replace the neotype with a well-documented specimen that agrees with other known specimens from Ambon and surrounding islands. This will have the effect of synonymizing V. cerambonensis with V. indicus and making V. indicus a species endemic to the islands of the central Moluccas. Varanus chlorostigma is proposed as the valid name for the taxon occurring on New Guinea and surrounding islands. The third chapter is the description of V. semotus, a new species of the V. doreanus group from Mussau island in northern Papua New Guinea. It is described on the basis of molecular and morphological characters. Varanus semotus is the first endemic reptile described from Mussau, and the only member of the V. doreanus group that is known to occur on a remote oceanic island. It is the third monitor lizard recorded from the Bismarck Archipelago. The distribution of the related V. finschi is also discussed and narrowed down to New Britain. The fourth chapter is a re-description and re-validation of V. douarrha, a species originally described in 1830 by the French naturalist René Lesson. The original type specimen has been lost from the museum in Paris and the name was for a long time considered synonymous with V. indicus. With the description of V. finschi (1994) the name douarrha was designated a nomen dubium due to the possible sympatry of two species on New Ireland. An examination of the collections from New Ireland and recent fieldwork on New Ireland, Djaul and Lavongai showed that only one species of Varanus occur there confirming the identity of V. douarrha. Morphological and molecular studies further showed that this species is distinct from both V. indicus and V. finschi and warrants recognition as a valid species.